Helicobacter pylori seropositivity in psoriasis - Poudel, Pratima; Kayastha, Bhaskar M M; Karki, Anupama (Asian Journal of Medical Sciences, 2021)
Background: Psoriasis is a common inflammatory disease characterized by erythematous papules and plaques with silvery white scales. Recently, the role of H. pylori has been studied as a possible etiological factor. Various published studies conducted to see the association of psoriasis with H. pylori show conflicting results. Aims and Objective: The aim of this study was to find out the association of H. pylori infection in patients with psoriasis. Materials and Methods: Cross sectional comparative study was conducted in Outpatient Department (OPD) of Dermatology, Bir Hospital. Any patient presenting at dermatology OPD above 16yrs of age with psoriasis were taken as cases. Age and gender matched patients with skin disease other than psoriasis were taken as controls. The test was done by collecting 2ml of venous blood from each patient. The serum was separated by centrifuging the sample. All the patients were screened for Helicobacter pylori infection by using a commercially available immunochromatographic kit for the detection of immunoglobulin G antibody against H. pylori in the serum. Results: Chronic plaque psoriasis was the most common variant (72.2%) and there was no significant association between psoriasis type and gender. Male to female ratio was 1.61:1. The mean age of onset in male patients was 42.41years and mean onset of disease in females was 40.61years. Our study showed 21.3% of the psoriasis patients had the history of psoriasis in the family. Nail changes were noted in 40.42% of patients. Psoriatic arthritis was present in 3% of cases. In our study H. pylori infection was found in 25(53.19%) of psoriasis patients and 15(31.91%) of the controls. This showed that H. pylori infection was found higher in psoriasis patients than the controls and the difference was statistically significant (p=0.037). Conclusion: This study showed the higher prevalence of H. pylori infection in patients with psoriasis and the differences is statistically significant. It also showed that there is increased prevalence of H. pylori seropositivity with the severity of the disease and with increased duration of illness though it is not statistically significant.